The No-men of England: Tyne & Wear County Council and the failure of the Scotland and Wales Acts 1978. Issue 1 (2nd January 2018) - McLean, Iain
ABSTRACT: The Scotland and Wales Acts 1978 failed on multiple criteria. Although devolution of powers to Scotland and Wales was a principal policy of the UK Labour governments in office from 1974 to 1979, it was defeated in a guillotine vote in 1977. That defeat was orchestrated by the leaders of Tyne & Wear County Council, angry that a government of their own party was apparently neglecting their region in favor of Scotland. The project was rescued in two separate bills, but a further rebel amendment inserted a minimum assent condition in the required referendums. The people of Wales rejected the devolution they were offered. The people of Scotland accepted it, but by a margin that failed to cross the threshold. The resulting vote of confidence brought down the Labour government in March 1979. The role of Tyne & Wear County Council in killing the bills has never been fully acknowledged. The lessons of the story for current devolution policy are explored. Its lesson for relations between Scotland and the north of England are as fresh now as then. The border between Scotland and England is permeable while the United Kingdom remains a single country. Therefore any policy for tax transfers and public expenditure differentials must be fair to the English as well as to the people of the other three territories. The main relevant findings from fiscal federalism are presented.